Differentiation of stx1A gene for detection of Escherichia coli serotype O157: H7 and Shigella dysenteriae type 1 in food samples using high resolution melting curve analysis. Issue 7 (28th May 2020) - Pakbin, Babak; Akhondzadeh Basti, Afshin; Khanjari, Ali; Azimi, Leila; Karimi, Abdollah
Abstract: Escherichia coli serotype O157: H7 and Shigella dysenteriae type 1 as the Shiga toxin‐producing bacteria cause some acute gastrointestinal and extraintestinal diseases such as hemorrhagic uremic syndrome and bloody diarrhea in human. Stx genes are the key virulence factors in these pathogens. The aim of this study was to develop HRMA assay to differentiate stx1A gene for detection of E. coli serotype O157: H7 and Sh. dysenteriae type 1 and determine the prevalence of these pathogens in food samples using this method. PCR‐HRMA assay and gold standard methods have been carried out for identification of pathogens among 135 different food samples. We found HRMA method a sensitive and specific assay (100 and 100%, respectively) for differentiation of stx1A gene, consequently, detection of these pathogens in food samples. Also, the highest prevalence of E. coli serotype O157: H7 and Sh. dysenteriae type 1 harboring stx1A gene was observed in raw milk and vegetable salad samples, respectively. HRMA as a rapid, inexpensive, sensitive and specific method is suggested to be used for differentiation of stx1A gene to detect E. coli serotype O157: H7 and Sh. dysenteriae type 1 as the key pathogens for safety evaluation of food samples. Abstract : In this paper, we developed high resolution melting curve analysis method to differentiate stx1A gene to detect Escherichia coli serotype O157: H7 and Shigella dysenteriae strains in food samples. We found this method specific and sensitive for detection of these pathogens in food samples. Also, we investigated the prevalence of these foodborne pathogens in food samples using this method. We observed the highest prevalence of E. coli serotype O157: H7 and Sh. dysenteriae type 1 in raw milk and vegetable salad samples, respectively. We found this method appropriate for detection of these pathogens in naturally contaminated food samples.